2009
DOI: 10.1007/s10600-009-9268-3
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antimicrobial and antioxidant activity of Seseli rigidum flower essential oil

Abstract: The natural products industry is currently looking for natural therapeutics and preservatives that can replace synthetic preparations. The scientific literature has identified new applications and uses of both traditional and exotic essential oils.Fungal and bacterial infections are important problems in phytopathology, agriculture, the food industry, and especially in medicine. Bacterial resistance to antimicrobial agents has become a serious problem worldwide, with resistance mechanisms having been identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 20 publications
0
17
0
2
Order By: Relevance
“…The results obtained by Stojković et al [23] on the essential oil content of S. rigidum, showed the values presented in µl/ml. They used the same strain of E. coli (ATCC 25922) and the result for MIC was 50 µl/ml and MMC at 100 µl/ml.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The results obtained by Stojković et al [23] on the essential oil content of S. rigidum, showed the values presented in µl/ml. They used the same strain of E. coli (ATCC 25922) and the result for MIC was 50 µl/ml and MMC at 100 µl/ml.…”
Section: Discussionmentioning
confidence: 90%
“…To the best of our knowledge, phytochemical analyzes of S. rigidum was done only in the case of essential oil composition and activity, both in the whole plant, and their parts [14,15,23]. These studies have shown that α-pinene, camphene, ß-pinene and limonene are main constituent of the essential oil with potential antimicrobial and antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…Limonene was absent in the Bulgarian plant, but reached 10% in the Serbian sample. The content of sabinene varied between 6.5 and 39.8% in the different plant parts of S. rigidum of Bulgarian origin, while its amount was 1.4, 4.0 and 5.5% in the Serbian samples, respectively [4][5][6]. The discussed differences could be due to environmental conditions or to existence of chemotypes of this endemic species.…”
mentioning
confidence: 88%
“…Finally, the obtained results were compared with those published in the literature for the same species collected in Serbia [ [4][5][6]. Monoterpene hydrocarbons seem to be characteristic of S. rigidum aerial parts as their amount in all samples is greater than 68% and reaches 90% in the leaves of the Bulgarian sample.…”
mentioning
confidence: 93%
See 1 more Smart Citation